Neural correlates of tobacco cue reactivity predict duration to lapse and continuous abstinence in smoking cessation treatment. (6th September 2017) - Owens, Max M.; MacKillop, James; Gray, Joshua C.; Beach, Steven R.H.; Stein, Michael D.; Niaura, Raymond S.; Sweet, Lawrence H.
Abstract: It has been hypothesized that neural reactivity to drug cues in certain limbic/paralimbic regions of the brain is an indicator of addiction severity and a marker for likelihood of success in treatment. To address this question, in the current study, 32 participants (44 percent female) completed a functional magnetic resonance imaging cigarette cue exposure paradigm 2 hours after smoking, and then enrolled in a 9‐week smoking cessation treatment program. Neural activation to smoking cues was measured in five a priori defined limbic/paralimbic regions previously implicated with cue reactivity across substances. These included regions of the ventral striatum, anterior cingulate cortex and amygdala. Cox proportional hazard modeling was conducted to predict the number of days to first smoking lapse by using neural activation in these regions. Greater neural activation during pre‐treatment exposure to smoking cues in the right ventral striatum, the left amygdala, and the anterior cingulate was associated with longer periods of abstinence following cessation. A similar pattern was present for continuous abstinence for the full duration of treatment. While baseline levels of nicotine dependence were strongly associated with treatment outcome, activation in the right ventral striatum predicted duration of abstinence beyond level of nicotine dependence. These results suggest that pre‐treatment reactivity to smoking cues in areas associated with cue reactivity may be associated with successfully maintaining abstinence during treatment. This is consistent with models that propose that as addiction becomes more severe, motivational processing shifts from regions that subserve reward salience and learning to regions responsible motor behavior and habit learning. Abstract : Reactivity to cues associated with smoking is an established feature of tobacco use disorder. This human fMRI study predicts lapse and continuous abstinence in smoking cessation treatment using brain response to visual cigarette cues in the ventral striatum, amygdala and anterior cingulate cortex. Contrary to prior research, greater activation to smoking cues in these regions was associated with a longer duration of abstinence after quitting and greater likelihood of maintaining abstinence throughout treatment.